Parallel Boundary Elements Using OpenMP - Cunha, M. T. F.; Coutinho, A. L. G. A.; Telles, J. C. F. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
This work presents our efforts towards single node optimization and parallelization of an existing Boundary Element Method (BEM) code using OpenMP. Basic techniques of High Performance Computing (HPC) are employed to enhance serial code performance and to identify code parts to be parallelized. Numerical experiments on a SGI Origin 2000 on large problems show the effectiveness of the proposed approach.